EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA PADA DESA TANJUNG MORAWA A, KECAMATAN TANJUNG MORAWA, KABUPATEN DELI SERDANG - Zenni Riana; Lulu Nada Lubis (Universitas Islam Islam Sumatera Utara, 2020)
The research to Effectiveness of Management of Village Fund Allocation in Tanjung Morawa A Village, Tanjung Morawa District, Deli Serdang Regency. Allocation of village funds is funds sourced from the central government. Therefore, it was found that there were problems regarding the allocation of village funds in TanjungMorawaA village, TanjungMorawa District. That village fund allocation is less effective. Based on the description, this study formulates the existing problem 1) How is the effectiveness of the management of Village Fund Allocation in TanjungMorawa A village, 2) what factors influence the effectiveness of the management of Village Fund Allocation in TanjungMorawa A. And this study aims to find out 1) to analyze and explain the management effectiveness of Village Fund Allocation in TanjungMorawa A village, 2) to analyze and explain the factors that affect the management effectiveness of Village Fund Allocation in TanjungMorawa village A. Analysis of data used is effectiveness techniques and effectiveness ratio of the Ministry of Home Affairs, Ministry of Home Affairs. Data was collected using the method of documentation and interviews.The results showed that the Effectiveness of Village Fund Allocation Management in TanjungMorawa A Village, TanjungMorawa A District, The level of effectiveness of village fund management in TanjungMorawa A village was in 2015 (63.47%), 2016 (75.01%) and 2017 ( 83,60%). The inhibiting factor experienced in realizing village fund allocation in TanjungMorawa A village is the community's understanding of village fund allocation, miss communication, and human resources.